Construction of a Multiple English Teaching Mode Based on Cloud Technology - Xu, Ying (International Journal of Emerging Technologies in Learning (iJET), 2018)
In order to explore the construction of multiple English teaching ("learner-centered and teacher-led" classroom teaching + autonomous learning + interactive learning + multiple evaluation) mode based on cloud technology, a teaching system and operation procedures of new English teaching model are designed based on cloud technology. The design is completed through the analysis of the construction of mul-tiple teaching mode under cloud technology and the introduction to multiple English language teaching steps. In addition, the English teaching modes under the traditional English teaching are compared with those based on cloud technology. Finally, the application of multiple teaching mode under cloud technology is analyzed. The results showed that multiple English teaching mode under cloud technology perfectly complied with the English teaching under modern conditions. To sum up, the proposed method plays a significant role in promoting the English teaching mode, which is worthy of further study and utilization.